NOMINATIVE-PHRASEOLOGICAL CONSTRUCTING OF THE CONCEPT BREXIT IN THE ENGLISH LANGUAGE INTERNET DISCOURSE - BONDARENKO, Snizhana (My University, 2021)
Research Supervisor- Doctor of Philological Sciences, Professor Serebryanska I.M.